Ecological Rationality: A Framework for Understanding and Aiding the Aging Decision Maker - Mata, Rui; Pachur, Thorsten; Von Helversen, Bettina; Hertwig, Ralph; Rieskamp, Jörg; Schooler, Lael (Frontiers in Neuroscience, 2012)
Ecological rationality sees human rationality as the result of the adaptive fit between the human mind and the environment. The concept of ecological rationality focuses the study of cognition on two key questions: First, what are the environmental regularities to which people’s decision strategies are matched, and how frequently do these regularities occur in natural environments? Second, how well can people adapt their use of specific strategies to particular environments? Research on aging suggests a number of changes in cognitive function, for instance, deficits in learning and memory that may impact decision-making skills. However, it has been shown that simple strategies can work well in many natural environments, which suggests that age-related deficits in strategy use may not necessarily translate into diminished decision performance. Consequently, we argue that predictions about the impact of aging on decision performance depend not only on how aging affects decision-relevant capacities but also on the decision ecology in which decisions are made. In sum, we propose that the concept of the ecological rationality is crucial to understanding and aiding the aging decision maker.